Análise comparativa da resistência à corrosão de aços carbono em ensaios de campo e testes eletroquímicos - Edelize Angelica Gomes (2013)
as Low carbon steel is a very interesting material for many kind of industries. Carbon steel have low resistance and high hardness and high toughness and ductility. They are machinable and weldable, and has low production cost. Despite its limited corrosion resistance, carbon steel has been used in large-scale in marine applications, nuclear industry, fossil fuel plants energy, transportations, chemical processing, petroleum production and refining, pipelines, mining, construction and equipment for processing. The present work aims to compare the corrosion resistance of unpainted carbon steels using a field test in marine atmosphere and electrochemical tests in saline electrolytes. Low carbon steel containing different contents of alloying elements was studied; one of them is considered a weathering steel. The marine atmosphere studied is at Arraial do Cabo/RJ, the period of field tests was eight years, and the eletrochemical tests used were eletrochemical impedance spectroscopy and Tafel analysis. The morphology and composition of the rust layer were studied using scanning electron microscopy and spectroscopy of dispersive energy, X-ray diffraction and X- ray fluorescence. The rust layer with a higher content of lepidocrocite and goethite were found in steels with a lower corrosion rates and a higher values of polarization resistance. The corrosion rate of the samples exposed in the field testing was low for the JQ0017 JQ0013-19-19 steels. The phases identified in corrosion layers on steels exposed to marine atmosphere were goethite, lepidocrocite, magnetite, and akaganeite. Measurements of electrochemical impedance spectroscopy showed that the JQ0013-19 steel showed the best performance against corrosion in aqueous solutions of NaCl 3.5 w/v and NaCl 10% w/v. The JQ0017 steel showed the second highest value of polarization resistance in saline solution of NaCl 10% w/v among the carbon steels studied. The technique of electrochemical impedance spectroscopy allowed distinguishing the steels according to the corrosion behavior in saline media.